Training of Trainer Kasipang (Psychoeducation of Pro-Environmental Behavior) on Guidance and Counseling Teachers in Banjar Regency - Rika Vira Zwagery; Neka Erlyani; Rahmi Fauzia; Marina Dwi Mayangsari (Jurnal Berkala Kesehatan, 2023)
One way to overcome and prevent that can be done to increase student awareness and shape pro-environmental behavior is through the learning process with psychoeducational methods. Psychoeducation is not carried out directly to students, but is taught to teachers through the "KASIPANG" Training of Trainer program. This program aims to equip teachers with knowledge and skills in forming pro-environmental behavior in students because teachers play an important role in shaping student behavior in schools. The Training of Trainer program is carried out through lectures, discussion and role-playing methods. The teachers who participated in the training were given the material on ways to form pro-environmental behavior with 3 techniques as research that had been done before, namely Psychoeducation of Pro-environmental Behavior, Symbolic Modeling and token economy. Based on the results of the evaluation, it was found that 92% of participants were satisfied with the services provided, 92% of participants considered that the presenters had good mastery of the material, 91% of participants considered satisfied with the activities carried out and 97% of participants were satisfied with the facilities provided. In addition, based on the follow-up, it was found that 100% of the participants expressed an increased understanding of pro-environmental behavior, pro-environment behavior change techniques through modeling and token economy.